Basic theories of openness, transparency and accountability in state governance and anti-corruption - Dang, Minh Tuan (Tư pháp - Hà Nội, 2020)
Openness , transparency and accountability are the basic elements of good governance and prevention of corruption in governance . Being studied for a long time , they have become the popular principles applied in public governance and anti - corruption in the context of new theories of governance that acknowledge and increasingly promote the participation of people in governance . However , some theoretical issues on this topic are not clarified and comprehensively understood . In particular , there are still many problems of these principles implementation in different practical contexts. This article clarifies the concepts , roles and conditions to ensure openness , transparency and accountability in state governance ( public governance ) and anti - corruption . It contributes to the clarification of some concepts and suggest a number of conditions to ensure this implementation